Accumulation of talin in nodes at the edge of the lamellipodium and separate incorporation into adhesion plaques at focal contacts in fibroblasts (The Rockefeller University Press, 1991)
The focal contact forms beneath F-actin-rich ribs, or cytoplasmic precursors, present in the lamellipodia of fibroblasts. The basal part of the precursor is retained at the contact as the initial adhesion plaque. We have examined the distribution of talin in the lamellipodia and adhesion plaques of chicken embryo fibroblasts relative to the process of focal contact formation. Motility of single cells was recorded with differential interference contrast or interference reflection microscopy before fixation and fluorescent staining for talin, F-actin, and vinculin. Talin is present along the extreme edge of the lamellipodium, where it is further concentrated into a series of nodes. The nodes of talin are present at the tips of both larger and finer F-actin-rich ribs and at small structural nodes at the edge of the lamellipodium. We suggest that the talin in the nodes functions, via a cross-linking activity, in the convergence of actin filaments at the membrane during development of the ribs. Talin accumulates de novo in the adhesion plaque, independent of that at the tip of the precursor, in response to contact with the substrate. This second accumulation of talin at the focal contact starts before vinculin, consistent with a sequential binding of talin at the membrane and of vinculin to talin. The results imply that talin functions independently at two steps during formation of the focal contact: the development of the F-actin-rich precursor of the contact; and development of the contact-associated adhesion plaque, both involving organization of F- actin at the membrane.